ECONOMIC EFFECTS OF DIFFERENT THINNING PROGRAMS of Pinus elliottii - Spathelf, Peter (2000)
The effect of different thinning programs (light thinning, medium and heavy thinning) on the internal rate of return was studied in stands of Pinus elliottii. The sampled stands were planted in 1976 with an inicial spacing of 2 x 2 m. Thinning intensity was expressed by the stand density index  of   Reinecke  (SDI). Thinned   volume   was   determined   using   the   assortment  tables  of SCHNEIDER & OESTEN (1991) and costs/prices of the year 1998 of the Association of Forest Enterprises of Rio Grande do Sul (AGEFLOR). The highest internal rate of return was obtained with a light thinning with a rotation length of 15 years and an initial density of 2500 trees. The lowest internal rate of return resulted from a light thinning, but in 45 years and with an initial density of 1500 trees.  In general,  the  internal  rate  of  return  diminished  with increasing rotation length. A sensitivity analysis showed that timber price was the most sensitive variable to influence profitability.